Fluid-Triggered Aftershocks in an Anisotropic Hydraulic Conductivity Geological Complex: The Case of the 2016 Amatrice Sequence, Italy - Convertito, Vincenzo; De Matteis, Raffaella; Improta, Luigi; Pino, Nicola Alessandro (Frontiers in Earth Science, 2020)
The mechanism by which faults interact each other is still a debated matter. One of the main issues is the role of pore-pressure diffusion in the delayed triggering of successive events. The 2016 Amatrice-Visso-Norcia seismic sequence (Central Apennines, Italy) provides a suitable dataset to test different physical mechanisms leading to delayed events. The sequence started on August 24, 2016, with the Amatrice mainshock (MW = 6), and was followed after more than 60 days by events in Visso (MW = 5.4) and Norcia (MW = 5.9). We analysed the contribution of the static stress change and the role of fluids in the delayed triggering. Through 3D poroelastic modelling, we show that the Amatrice mainshock induced a pore-pressure diffusion and a normal stress reduction in the hypocentral area of the two aftershocks, favouring the rupture. Our parametric study employs a simple two-layered conductivity model with anisotropy in the seismogenic layer, characterized by larger conductivity values (K>10-5 m/s) along the NNW-SSE direction. The one-way coupled pore-pressure 3-D diffusion modelling predicts the maximum increase of the pore pressure at the location of the two Visso earthquakes 60 days after the mainshock. The occurrence of anisotropic diffusivity is supported by the pattern of active faults and the strong crustal anisotropy documented by S-wave splitting analysis. We conclude that the temporal evolution of the sequence was controlled by the anisotropic diffusion of pore-pressure perturbations through pre-existing NNW-trending fracture systems.